Extracellular Volume by Computed Tomography Is Useful for Prediction of Prognosis in Dilated Cardiomyopathy Cases with Heart Failure with Reduced Ejection Fraction - Satomi Yashima; Hiroyuki Takaoka; Joji Ota; Moe Matsumoto; Yusei Nishikawa; Yoshitada Noguchi; Shuhei Aoki; Kazuki Yoshida; Katsuya Suzuki; Makiko Kinoshita; Haruka Sasaki; Noriko Suzuki-Eguchi; et al. (Journal of Cardiovascular Development and Disease)
Objective: Cardiac computed tomography (CT) helps screen coronary artery stenosis in cases with dilated cardiomyopathy (DCM). Extracellular volume fraction (ECV) analysis has recently been eligible for CT. Method: We evaluated the impact of ECV on the CT to predict the prognosis in DCM patients with heart failure with reduced ejection fraction (HFrEF). Patients or Materials: We analyzed 101 consecutive DCM cases with HFrEF who underwent cardiac CT. All the patients had a lower left ventricular (LV) ejection fraction (LVEF) of less than 40%. We evaluated the effect of ECV to predict the patients’ prognosis. Cardiovascular death, hospitalization due to heart failure, and fatal arrhythmic events were included in the major adverse cardiac events (MACE). Results: MACE occurred in 27 cases (27%). The patients with MACE (27 cases) had an increased ECV on the LVM on the CT (37.2 ± 6.7 vs. 32.2 ± 3.6%, p = 0.0008) compared to the others (74 cases). Based on the receiver operating characteristics curve analysis, the best cutoff value of the ECV on the LVM to predict the MACE was 32.3%. The patients with ECV ≥ 32.3% had significantly higher MACE based on the Kaplan–Meier analysis. The ECV on the LVM was a significant marker to predict MACE based on the univariate Cox proportional hazard model (hazard ratio of 8.00, 95% confidence interval 1.88–33.97, p = 0.0048). Conclusions: ECV by CT is helpful to predict MACE in cases with DCM and HFrEF.